THU0469 Genetic Variants in IL-6, IL-10, C5-TRAF1 and FCRL3 and Progression of Joint Damage in Rheumatoid Arthritis; A Study on Six Cohorts. (10th June 2014) - van Steenbergen, H.W.; Rodríguez-Rodríguez, L.; Rantapää-Dahlqvist, S.; Berglin, E.; Huizinga, T.W.; Fernández-Gutiérrez, B.; Gregersen, P.K.; van der Helm-van Mil, A.H.
Abstract : Background: Thanks to the introduction of novel treatments and up-to-date treatment strategies, the severity of joint destruction in rheumatoid arthritis (RA) has decreased considerably. Nonetheless, in daily clinical practice radiographic progression is still prevalent. Understanding the mechanisms underlying the inter-individual differences in radiographic progression is relevant and heritability studies have shown that genetic factors explain part of these inter-individual differences. Indeed, some genetic variants have been identified and replicated in independent studies or found significant in meta-analyses. The literature on genetic variants and joint destruction in RA was systematically reviewed recently; for genetic variants in C5-TRAF1, IL6, IL10 and FCRL3 the existing literature was indefinite on whether these variants are associated with joint destruction (Krabben et al, in press). Objectives: We aimed to clarify the relevance of these genetic variants for RA severity and studied these genetic variants in relation to radiographic progression in RA patients included in six independent cohorts. Methods: In total 5, 952 sets of radiographs of 2, 495 RA patients were studied. These patients were largely included in era before the introduction of biologics, in cohorts in the Netherlands, Sweden, Spain and three cohorts from the USA. In five cohorts genotyping was done using the Immunochip according to Illumina's protocols and in one cohort (NARAC) genotyping was performed using the Illumina Hapmap500 BeadChip. Genotyping data of rs2900180 in C5-TRAF1, rs1800795 in IL6, rs1800896 in IL10 and rs7528684 in FCLR3 were extracted. Associations with radiographic progression rates were tested per cohort using an additive model, adjusting for age, gender and treatment when appropriate. The results on yearly radiographic progression rates were combined in inverse variance weighted meta-analyses. Analyses were done on the total RA population and after stratification for anti-citrullinated peptide antibodies (ACPA). Results: No significant associations were found for rs1800795 in IL6, rs1800896 in IL10 and rs7528684 in FCLR3 ; neither in the total population nor in ACPA-positive or ACPA-negative RA. Also the directionality of the effects was diverse. Although for rs2900180 in C5-TRAF1 no significance was obtained in the total population nor in ACPA-positive RA, an association was observed in ACPA-negative RA (p value meta-analysis 2.7x10 –6 ). In all data sets with ACPA-negative RA patients, the minor allele was associated with a higher rate of joint destruction. Conclusions: In contrast to initial reports, variants in IL-6, IL-10 and FCLR3 were not associated with radiographic progression in the present large meta-analyses. Although an association between rs2900180 in C5-TRAF1 and joint destruction was initially identified in the total RA population, we here replicated an association with the joint destruction rate in ACPA-negative RA. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2860